ESG as a Moderating Force: How Capital Structure and Dividend Policy Shape Firm Value - Flavian Gunawan; Bagas Brian Pratama (CV Edujavare Publishing, 2026)
Firm value remains a key concern in corporate finance, particularly as investors increasingly consider sustainability performance alongside traditional financial indicators. This study examines the effects of capital structure and dividend policy on firm value and investigates whether Environmental, Social, and Governance (ESG) performance moderates these relationships among firms included in the IDX ESG Leaders Index. Using a quantitative causal approach, the study analyzes panel data from 26 companies over the 2021–2024 period (104 firm-year observations). Data were analyzed using panel regression and Moderated Regression Analysis (MRA) with the Fixed Effect Model (FEM) and White Cross-Section robust standard errors. The results indicate that capital structure and dividend policy do not significantly affect firm value. ESG performance also does not moderate the relationship between capital structure and firm value. However, ESG significantly moderates the relationship between dividend policy and firm value in a negative direction, suggesting that stronger ESG performance weakens the value relevance of dividend payouts. These findings imply that ESG and dividend policy may act as substitute signals of firm quality, where investor confidence generated through sustainability performance reduces the marginal importance of dividends as a valuation signal. The study highlights the selective role of ESG in influencing firm value within Indonesia’s sustainability-oriented capital market.